(3NQjOI GdbUQ hLQjOI GdYUQs - (3eMeO Hf eMeO MGeO GdCUHgGfj, YeGO GdOjf GdcGJH,J (B597 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO HCKfGA GdJQLeI GdJi bHd JQLeI Gdedc Jbi GdOjf Hf TGgfTGg HgPG GdHjJ (B: (3bO SCd bO CSGd ShGAg WQai aNGdW QHYg GdeJQbQbG s
(3BNQgG (B:s
(3hGSJTgO GHf QhGLI GdePchQ ai GdeYScQ GdUdGMi GdfGUQi Je GdLR AGdSGOS hjJdhg GdLRA GdSGHY hgh GdKGfi ef GdbSe GdKGdK s
(3LRA ef GdbSe GdKGdK ai TYQGA GdTGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B26s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs